2021
DOI: 10.1002/ange.202104924
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Galectin Mimic

Abstract: Galectins are a galactoside specific subclass of carbohydrate binding proteins (lectins) involved in various cellular activities, certain cancers, infections, inflammations, and many other biological processes. The molecular basis for the selectivity of galectins is well‐documented and revolves around appropriate interaction complementarity: an aromatic residue for C−H⋅⋅⋅π interactions and polar residues for (charge assisted) hydrogen bonds with the axial hydroxyl group of a galactoside. However, no synthetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 71 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…This investigation revealed that preorganization can adversely impact carbohydrate recognition. In addition, similar cages were prepared as synthetic Ca 2+ ‐dependent lectin mimics, [101] octyl mannoside receptors, [102] and synthetic galectin mimics [103] . Introducing four pendant guanidium chains as solubilizing groups, a water‐soluble cage was developed that could selectively recognize anionic monosaccharide N‐Acetylneuraminic acid (NANA) with moderate binding affinity [57] .…”
Section: Dynamic Bond‐based Receptorsmentioning
confidence: 99%
“…This investigation revealed that preorganization can adversely impact carbohydrate recognition. In addition, similar cages were prepared as synthetic Ca 2+ ‐dependent lectin mimics, [101] octyl mannoside receptors, [102] and synthetic galectin mimics [103] . Introducing four pendant guanidium chains as solubilizing groups, a water‐soluble cage was developed that could selectively recognize anionic monosaccharide N‐Acetylneuraminic acid (NANA) with moderate binding affinity [57] .…”
Section: Dynamic Bond‐based Receptorsmentioning
confidence: 99%
“…However, achieving effective recognition of polar species like saccharides in water leveraging a biomimetic approach is a non‐trivial task [22,23] . Indeed, milestones in this field have been achieved only recently, mainly by means of sophisticated macrocyclic architectures [24–30] . In contrast, acyclic receptors have been largely unexplored, [31–34] although they may present distinct advantages over macrocyclic structures in terms of simpler synthesis, more easily modifiable structure, easy adaptability to different guests and, most of all, the possibility of binding non‐terminal saccharide entities.…”
Section: Introductionmentioning
confidence: 99%
“…Carbohydrate is a critical component in various biological processes, [1,2] such as energy storage, intercellular communication, and immune response. Synthetic receptors [3–11] that bind carbohydrates have the potential to facilitate the investigation of their biological functions and the creation of new therapeutic and diagnostic agents, such as anti‐infective agents, synthetic antibodies, and carbohydrate sensors. The development of synthetic receptors [12–14] for glucose, in particular, holds significant implications for managing blood glucose levels in diabetes.…”
Section: Introductionmentioning
confidence: 99%